Digitizing Local Archives and North Sumatera Culture through Literacy Using the E-Library Website - Maulina, Intan; Harahap, Muhammad Khoiruddin (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Digitizing local archives and culture through literacy using an e-library website is a reflection as well as an effort to save phenomenal memories which are unique and hardly repeated. An archive is a crucial component of social life and literacy, and it must be conserved because of its historical significance. Archives need to be preserved because the nation’s cultural treasures due to the fact beyond activities documented via data are legal evidence. Technology and information advancements are one of the options that can be used by the public to store online documentation and archiving. Literature can reflect the historical history of a country and are also a cultural driver in the cultural development of society. The type of research used in this study is library research. Data collection techniques were carried out by observation, documentation studies, and interviews at the five research locations, namely the North Sumatra Provincial Library and Archives Service, Tebing Tinggi City Library and Archives Service, Pematangsiantar Library and Archives Service, Regency of Central Tapanuli Library and Archives Service, Sibolga City Library and Archives Service and North Tapanuli Library and Archives Service. The result of this research is that the best library service was shown by the library in Tebing Tinggi, but the Regency of Central Tapanuli Library and Archives Service area has an unprecedented and excellent collection of books and they have got an e-library from Kubuku as a digital library for society.